Occlusion of Fontan fenestrations using the Amplatzer septal occluder. Issue 4 (1st April 1998) - Tofeig, M; Walsh, K P; Chan, C; Ladusans, E; Gladman, G; Arnold, R
Abstract : Objective: To evaluate the efficacy and safety of the Amplatzer septal occluder device for occlusion of Fontan fenestrations. Subjects: Five children aged 5–10 years who had undergone a fenestrated Fontan operation. Setting: Tertiary paediatric cardiology centre. Methods: Each patient had right and left heart catheterisation to assess haemodynamic suitability for fenestration closure. Sizing of the defect was achieved with a balloon wedge catheter and transoesphageal echocardiography. Transcatheter occlusion of the fenestration was accomplished using a 4 mm device in three patients, and 5 mm or 9 mm devices in the other two patients. Residual shunting following occlusion was assessed using angiography and echocardiography. Results: 100% occlusion rate of the fenestration was achieved in all patients. No complications or device failures were seen during the three month follow up period. Conclusion: The Amplatzer septal occluder device is safe, and effectively occludes the Fontan fenestration.